Investigation into the Mechanical Properties and Microstructure of a Local and an Imported Reinforcement Bar - Oisakede, Maureen Olere; Premlall, Kasturie; Popoola , Abimbola Patricia (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
This study investigates the mechanical properties and microstructure of locally manufactured and imported steel reinforcement bars, which are used in industrial and wastewater settings. Imported Steel (Brazilian steel) and local steel (Land craft industrial Steel) were used for the experiment. Tensile, hardness and impact tests were done and Optical microscope was employed to examine the microstructure of the steels before and after corrosion when immersed in 1 molar of sulphuric acid solution. Ultimate tensile strength for land craft industrial steel was 708.30 MPa, the yield strength 520 MPa while the % elongation was 25.64. However, for the Brazilian steel, ultimate tensile strength was 538.51 MPa, yield strength 525 MPa and % elongation was 16.32. The average hardness value for land craft industrial steel was 194.80 HV, while for Brazilian steel; the average hardness value was 182.38 HV. The impact result for land craft industrial steel and Brazilian steel were 41.03 J and 35.68 J respectively., the Brazilian steel depicted pitting corrosion that is wide, elliptical, and whitish, suggesting that the corrosion has a noticeable elongation in one direction while Local craft industrial steel was observed to have open and deep pits suggesting a localized form of corrosion.